Salivary gland macrophages in health and disease: heterogeneity, niche crosstalk, and therapeutic avenues - Li, Xinglei; Feng, Yan; Xue, Huixin; Ni, Xinxin (Frontiers in Immunology, 2025)
Salivary glands (SGs) produce saliva essential for digestion, mucosal immunity, and as a source of non-invasive biomarkers. The health and pathology of SGs hinge upon a dynamic equilibrium between two core macrophage (Mφ) populations: long-lived, tissue-resident 'guardians' that maintain homeostasis, and short-lived, monocyte-derived 'sentinels' that mount rapid responses. This review posits an integrative framework wherein the disruption of this balance is a central pathogenic hub across diverse SG disorders, from autoimmunity to radiation-induced injury. We reconcile long-standing controversies over Mφ origins by proposing a 'developmental transition model' and highlighting the pivotal discovery of sexual dimorphism—a fundamental difference in Mφ maintenance between males and females. Drawing on advances in single-cell omics and spatial imaging, we redefine SG Mφ heterogeneity far beyond the M1/M2 paradigm, recasting them as critical 'communication hubs' within the neuro-epithelial-immune network. This new perspective inspires a paradigm shift in translational priorities, moving from broad immunosuppression towards precisely 'restoring ecological balance'. We prioritize therapeutic strategies such as selectively protecting guardian Mφs via transient Hedgehog pathway activation, and promoting regeneration through transplantation of engineered effective-mononuclear cells (E-MNCs), a strategy with emerging clinical validation. Furthermore, we survey the frontier of targeting tumour-associated Mφs and underscore the immense potential of developing non-invasive salivary biomarkers for immune monitoring, charting a course to bridge critical translational gaps.